In Silico Evaluation of Enzymatic Tunnels in the Biotransformation of α-Tocopherol Esters - Azevedo, Tamara Stela Mendonça; Silva, Lavínia Kelly Barros; Lima, Álvaro Silva; Pereira, Matheus Mendonça; Franceschi, Elton; Faria Soares, Cleide Mara (Frontiers in Bioengineering and Biotechnology, 2022)
Motivation: α-tocopherol is a molecule obtained primarily from plant sources that are important for the pharmaceutical and cosmetics industry. However, this component has some limitations such as sensitivity to oxygen, presence of light, and high temperatures. For this molecule to become more widely used, it is important to carry out a structural modification so that there is better stability and thus it can carry out its activities. To carry out this structural modification, some modifications are carried out, including the application of biotransformation using enzymes as biocatalysts. Thus, the application of a computational tool that helps in understanding the transport mechanisms of molecules in the tunnels present in the enzymatic structures is of fundamental importance because it promotes a computational screening facilitating bench applications Objective: This work aimed to perform a computational analysis of the biotransformation of α-tocopherol into tocopherol esters, observing the tunnels present in the enzymatic structures as well as the energies which correspond to the transport of molecules. Method: To carry out this work, 9 lipases from different organisms were selected, their structures were analyzed identifying the tunnels (quantity, conformation, possibility of transport) and later the calculations of substrate transport for the biotransformation reaction in the identified tunnels. Additionally, the transport of the product obtained in the reaction through the tunnels was also carried out. Results: The enzymes with fewer tunnels were RML (3 tunnels), LBC and RNL (4 tunnels) PBLL (5 tunnels), CALB (6 tunnels), HLG (7 tunnels), LCR and LTL (8 tunnels) followed and the enzyme with the largest number of tunnels was the LPP (39 tunnels). However, the enzyme that had the greatest probability of transporting substrates concerning the biotransformation of α-tocopherol was CALB, as it obtains conformational and transport characteristics of molecules with a particularity. LPP has several tunnels in its structural conformation, however, possible reaction probabilities were not obtained with this biocatalyst.